2000
DOI: 10.1007/bf03028082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galvanic corrosion between precipitate and matrix on corrosion behavior of As-cast magnesium-aluminum alloys

Abstract: In the present study, the corrosion behavior of an as-cast magnesium alloy was studies focusing on the galvanic corrosion between a precipitate and Mg-rich matrix. Through immersion and electrochemical tests, the variation of the corrosion behavior with the alloy composition and alloy system was discussed in detail. The corrosion rate of an as-cast alloy increased abruptly to 9 wt.% A1 in both alloys, but in the composition range of over 12 wt.% A1, the corrosion rate reveals a different tendency than the allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…It was reported in our previous study [9] that the corrosion resistance of the as-cast AZ91D alloy is improved by the refinement of the grain size. It was also reported that the corrosion property of a precipitate is different depending upon the alloy system, and the corrosion behavior of an Mg-rich matrix operates as a dominant factor on galvanic corrosion between a precipitate and an Mgrich matrix in the a~s-cast alloy [10]. However, the understanding of the corrosion behavior of each component which composes of the microstrucmre of an as-cast/heat treated alloy is very significant to the enhancement of corrosion resistance of Mg alloys.…”
Section: Introductionmentioning
confidence: 97%
“…It was reported in our previous study [9] that the corrosion resistance of the as-cast AZ91D alloy is improved by the refinement of the grain size. It was also reported that the corrosion property of a precipitate is different depending upon the alloy system, and the corrosion behavior of an Mg-rich matrix operates as a dominant factor on galvanic corrosion between a precipitate and an Mgrich matrix in the a~s-cast alloy [10]. However, the understanding of the corrosion behavior of each component which composes of the microstrucmre of an as-cast/heat treated alloy is very significant to the enhancement of corrosion resistance of Mg alloys.…”
Section: Introductionmentioning
confidence: 97%
“…Based on the latest investigations, Ca, Mn and Zn elements are appropriate constituents that gradually degrade within the human body, along with magnesium, without raising the serum Mg 2+ level or damaging important organs such as kidneys 7,12,13 . Such particular elements, especially calcium, are contributing factors to control corrosion rate of magnesium alloys 14 . Ca is also one of the most important and necessary element of human bone, particularly in terms of chemical signaling with different cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Because its chemical identity has been simply recognized as the Mg~TAI,~ phase in stoichiometric form, some ambiguous interpretations for experimental results have often arisen [5,6]. However, in our previous study, it was reported that the chemical composition of the precipitate has a remarkable effect on the corrosion behavior of as-cast magnesium alloy [7,8]. In the present study, we aimed at investigating the chemical identity of the precipitate in as-cast Mg-xAl-lZn alloy and to suggest the slope of the calibration curve (volume fraction of precipitate vs. intensity ratio(I~,/IM~)) for the measurement of the fraction of precipitate.…”
Section: Introductionmentioning
confidence: 99%